A Preliminary Examination of a Strengths-Based Treatment for Adolescent Substance Use Issues - Harris, Nicholas; Brazeau, James N. R.; Rawana, Edward P.; Brownlee, Keith; Mazmanian, Dwight (Canadian Journal of Counselling and Psychotherapy, 2016)
Adolescent substance use disorders are a major public health concern. Given the many challenges associated with treating this population, ongoing research in this area is imperative. The purpose of the current study was to provide a preliminary examination of the substance use outcomes associated with an adolescent residential treatment program that utilizes a strengths-based approach. The current study examined treatment outcomes in 61 adolescents (aged 14 to 18 years) who completed a 5-week strengths-based residential treatment program for adolescent substance use issues. Results showed significant reductions in frequency of alcohol and marijuana use from pretreatment to 3 and 6 months posttreatment, and in opioid use frequency from pretreatment to 3 months posttreatment. In addition, changes in self-reported substance use goal progress scores indicated significant improvements in goal progress from pretreatment to 3 months posttreatment; these improvements were maintained at 6 months posttreatment. Finally, depressive symptomology was also found to decrease significantly from pretreatment to posttreatment, and this decrease was found to be predictive of better substance use outcomes at 6 months posttreatment. These findings add to the literature by providing preliminary data that support the utility of the strengths-based approach in the treatment of adolescence substance use issues.